Pulmonary mycobiome of patients with suspicion of respiratory fungal infection – an exploratory study - Oliveira, Mariana (2020)
Objective: This pilot study aimed to characterize the pulmonary mycobiome of patients with suspicion of fungal infection of the respiratory tract as well as to identify potentially pathogenic fungi colonizing/infecting their lungs. Methods: A cohort of 10 patients was analyzed, including HIV+ patients and patients with active infection caused by Mycobacterium species. Their respiratory samples (bronchoalveolar lavage fluid/ bronchial secretions) were pre-treated with lyticase and proteinase K; DNA was extracted using the High Pure PCR Template Preparation kit following the manufacturer’s instructions. The internal transcribed spacer region 1 (ITS1) and calmodulin gene were amplified by PCR and the resulting amplicons were sequenced using the Illumina MiSeq platform with pair-end reads of 150 bp. The obtained results were analyzed using the PIPITS pipeline as described by Gweon et al. [1]. Operational taxonomic units (OTU) to which less than 0.1% of the total reads attributed were disregarded. Results: Thirty-seven different OTU were identified from which two belonged to the Plantae kingdom, 11 had less than the 0.1% threshold of the total reads and were therefore disregarded. The remaining 24 different OTU (grouped in 17 phylotypes), were considered as part of the pulmonary mycobiome of patients. Two phyla were identified: Basidiomycota (33.3%) and Ascomycota (54.2%). Regarding the Basidiomycota phylum, reads were classified in three classes (Agaricomycetes, Tremellomycetes and Walleomycetes), while for the Ascomycota phylum four different taxonomical classes were identified: Pneumocystidomycetes, Dothideomycetes, Eurotiomycetes and Saccharomycetes, with the latter being the most frequent class. Twelve fungal genera were identified, being Candida the most frequently detected. The median number of fungal genera detected in patients’ pulmonary mycobiome was six (ranging from two up to nine). The genus Papilotrema and the potentially pathogenic genera Cryptococcus and Pneumocystis were exclusively found in the pulmonary mycobiome of HIV+ + patients. Other potentially pathogenic fungi such as Aspergillus spp., Trichosporon spp., Saccharomyces spp. and Schizophyllum spp. were also detected. Conclusion: This pilot study illustrates how the pulmonary mycobiome is rich and highly variable in patients with fungal infections. The obtained results suggest that the described metagenomic analysis may possess a great ability to quickly and effectively detect potentially pathogenic fungi in the mycobiome of patients, making it a promising future diagnostic tool. Thus, further optimization, standardization and clinical validation of these NGS methodologies should be warranted in the future.